The Case Study Of Pregnancy Midwife Care With Chronic Energy Deficiency (CED) - Ayu Endang Purwati; Sri Utami Asmarani; Syamimi Zulfana; Amsana Amsana; Rosidah Solihah (Yayasan Inspirasi El Burhani, 2023)
Introductions: Chronic Energy Deficiency (CED) is a condition where the mother suffers from a chronic shortage of food which results in health problems for the mother. CED can occur in women of childbearing age and in pregnant women. Someone is said to be at risk of CED if the Mid Upper Arm Circumference (MUAC) is < 23,5 cm. A state of prolonged energy deprivation in women of childbearing age and pregnant women is characterized by a MUAC of 23,5 cm. Aims: The purpose of this case study is to carry out midwifery care for pregnant women with Chronic Energy Deficiency (CED) with a midwifery care management approach, starting with a basic data review, data interpretation, identification of diagnoses or potential problems, determine the need for immediate action, midwifery care planning, implementation of midwifery care as needed and evaluation. Methods: The method used in this article is a descriptive method in the form of a case study with a midwifery approach. This case study uses a descriptive-analytical method, Results: The midwifery care process lasts for 6 months, with intensive assessment and monitoring of the client's condition to get good results. The formation of an understanding of the dangers of CED in pregnancy has succeeded in making the client comply with the consumption of the given and balanced food intake as recommended. Conclusions: The results of this care indicate that there is an increase in body weight and Mid Upper Arm Circumference (MUAC) in pregnant women with Chronic Energy Deficiency (CED) conditions influenced by proper midwifery care, especially in supplementary feeding and can be improved by providing correct and effective information according to client needs.